2009
DOI: 10.1042/bj20081466
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pancreatic stellate cell population with properties of progenitor cells: new role for stellate cells in the pancreas

Abstract: Numerous studies conducted in a diversity of adult tissues have shown that certain stem cells are characterized by the expression of a protein known as the ABCG2 transporter (where ABC is ATP- binding cassette). In the adult pancreas, although various multipotent progenitors have been proposed, the ABCG2 marker has only been detected in the so-called 'side population' (a primitive haematopoietic cell population with a multipotential capacity). In the present study we sought to identify new ABCG2+ pancreatic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…Stellate cells are mainly known as the primary collagenproducing cells following liver injury, which are responsible for fibrogenesis in chronic liver disease (85). In addition to a role for stellate cells in fibrogenesis, evidence exists that stellate cells have properties of stem cells (86)(87)(88)(89)(90)(91)(92). The expression of stem/progenitor cell-associated genes such as nestin in stellate cells of the liver and pancreas (86,89,(92)(93)(94) and the potential of stellate cells to differentiate into hepatocyte-like cells in vitro (86,92) indicate that stellate cells have stem cell characteristics.…”
Section: Figurementioning
confidence: 99%
“…Stellate cells are mainly known as the primary collagenproducing cells following liver injury, which are responsible for fibrogenesis in chronic liver disease (85). In addition to a role for stellate cells in fibrogenesis, evidence exists that stellate cells have properties of stem cells (86)(87)(88)(89)(90)(91)(92). The expression of stem/progenitor cell-associated genes such as nestin in stellate cells of the liver and pancreas (86,89,(92)(93)(94) and the potential of stellate cells to differentiate into hepatocyte-like cells in vitro (86,92) indicate that stellate cells have stem cell characteristics.…”
Section: Figurementioning
confidence: 99%
“…Reports regarding the potential origin of insulin-producing cells are extremely controversial, including bone marrow (BM)-derived progenitors, pancreas-resident stem cells, transdifferentiation of acinar as well as duct cells and self-duplication of adult β-cells [5][6][7][8][9][10]. Recently, Mato et al [11] reported an in vitro-selected mitoxantrone-resistant cell pool from rat pancreas displaying characteristics of PSCs. These cells were reported to differentiate into insulin-producing cells upon adequate stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the information about the activation mechanism has derived from in vitro studies of rodent PSC maintained in culture. These cultures, initially express the molecular markers of the quiescent cells and it is easy to observe the presence of the cytoplasmic lipid droplets by oil red stain (Apte MVet al, 1988, Mato E et al 2009. However, in a short amount of time, most of the cells in the culture showed a proliferative phenotype with -SMA and ECM protein expression.…”
Section: Biology Of Pancreatic Stellate Cellsmentioning
confidence: 99%
“…These intermediary filaments present in cells of the epithelial origin, such as ductal cells, indicate that the cell could be involved in the mechanism to control the mesenchymal-epithelial transition (MET). This phenomenon consists of a promising source of cells for replacement therapies, but can also be involved in the carcinogenesis process (Mato E et al 2009). …”
mentioning
confidence: 99%